The species of Symplocodes Hebard (Blattodea: Ectobiidae: Blattellinae) with description of a new species from China. Issue 5 (9th February 2016) - Zheng, Yuhong; Wang, Chenchen; Che, Yanli; Wang, Zongqing
Abstract: This paper provides a generic diagnosis, a species list and taxonomy for the genus Symplocodes Hebard, 1929. The new species Symplocodes euryloba sp. nov. from China is described and illustrated. Symplocodes tsaii Bey-Bienko, 1958 is regarded as a subspecies of Symplocodes marmorata (Brunner von Wattenwyl, 1893), i.e. S. marmorata tsaii comb. nov., and its differences from S. marmorata marmorata (Brunner von Wattenwyl, 1893) are discussed. Two known species, Symplocodes ridleyi (Shelford, 1912) and Symplocodes manubria Feng et Guo, 1990, are redescribed and illustrated, whereas one new specific synonym, i.e. Symplocodes brachialis, is proposed. A key to species worldwide is provided. The tarsal claws of these four species as well as one species of Chorisoserrata Roth, 1998 are examined and photographed to compare the intergeneric differentiation of claw specialization and to discuss its function.